Vagus Nerve Stimulation Improves Mitochondrial Dysfunction in Post–cardiac Arrest Syndrome in the Asphyxial Cardiac Arrest Model in Rats - Kim, Seonghye; Park, Inwon; Lee, Jae Hyuk; Kim, Serin; Jang, Dong-Hyun; Jo, You Hwan (Frontiers in Neuroscience, 2022)
Cerebral mitochondrial dysfunction during post–cardiac arrest syndrome (PCAS) remains unclear, resulting in a lack of therapeutic options that protect against cerebral ischemia–reperfusion injury. We aimed to assess mitochondrial dysfunction in the hippocampus after cardiac arrest and whether vagus nerve stimulation (VNS) can improve mitochondrial dysfunction and neurological outcomes. In an asphyxial cardiac arrest model, male Sprague–Dawley rats were assigned to the vagus nerve isolation (CA) or VNS (CA+VNS) group. Cardiopulmonary resuscitation was performed 450 s after pulseless electrical activity. After the return of spontaneous circulation (ROSC), left cervical VNS was performed for 3 h in the CA+VNS group. Mitochondrial respiratory function was evaluated using high-resolution respirometry of the hippocampal tissue. The neurologic deficit score (NDS) and overall performance category (OPC) were assessed at 24, 48, and 72 h after resuscitation. The leak respiration and oxidative phosphorylation capacity of complex I (OXPHOS CI) at 6 h after ROSC were significantly higher in the CA+VNS group than in the CA group (p = 0.0308 and 0.0401, respectively). Compared with the trends of NDS and OPC in the CA group, the trends of those in the CA+VNS group were significantly different, thus suggesting a favorable neurological outcome in the CA+VNS group. (p = 0.0087 and 0.0064 between times x groups interaction, respectively). VNS ameliorated mitochondrial dysfunction after ROSC and improved neurological outcomes in an asphyxial cardiac arrest rat model.